1976
DOI: 10.1007/bf00561183
|View full text |Cite
|
Sign up to set email alerts
|

Dopa-positive cells and melanin in basal cell epithelioma (BCE)

Abstract: In 47 out of 61 bce's, melanocytes were detectable with the aid of Dopa-reaction. In 24 of these cases, the percentage of tumour cells was less 5%, and in 23 it was more. The melanocytes preferred the periphery of the epithelial tumour formations. Only when the proportion of melanocytes exceeded 5% were they also to be found in the central parts of the tumours. Generally the melanocytes were more numerous in the upper parts of tumours, next to the epidermis. Our findings strengthen the opinion, that bce is a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
6
0

Year Published

1979
1979
2001
2001

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 11 publications
2
6
0
Order By: Relevance
“…The present ultrastructural study of pigmented BCCs has revealed alterations of melanocytes more extensive than that previously reported. 6–9,13–16 The ultrastructural morphometric findings obtained from this study confirmed, as expected, a statistically significant increase in melanocyte nuclear and cell area, nuclear and cell perimeter, and cell major diameter in the pigmented areas compared with the perilesional normal controls. The melanocytes in the pigmented areas exhibited hyperactivity of melanogenesis, and a degree of proliferation as shown by the presence of centrioles, in agreement with previous studies.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The present ultrastructural study of pigmented BCCs has revealed alterations of melanocytes more extensive than that previously reported. 6–9,13–16 The ultrastructural morphometric findings obtained from this study confirmed, as expected, a statistically significant increase in melanocyte nuclear and cell area, nuclear and cell perimeter, and cell major diameter in the pigmented areas compared with the perilesional normal controls. The melanocytes in the pigmented areas exhibited hyperactivity of melanogenesis, and a degree of proliferation as shown by the presence of centrioles, in agreement with previous studies.…”
Section: Discussionsupporting
confidence: 84%
“…Maloney et al 4 confirmed that the melanocytes were large and had hypertrophied dendritic processes in 90% pigmented BCCs, using Fontana‐Masson staining. Deppe et al 6 demonstrated that the melanocytes were localized predominantly in the periphery of the BCC, using the Dopa‐reaction. When the proportion of melanocytes exceeded 5%, they were also observed in the central parts of tumors, a phenomenon described as melanocyte colonization.…”
mentioning
confidence: 99%
“…In the white races, the frequency of pigmented BCC varies from 6.7% to 33% (19,20). As in the previous studies (20,21), pigment was located in superficial tumor islands more commonly than in deep ones. A notable finding was that only 28.6% (2 out of 7) of the fibrosing type was microscopically pigmented, in contrast to 100% (4 out of 4) in the adenoid type, 72.3% (34 out of 47) in the solid type, and 66.7% (6 out of 9) in the superficial type.…”
Section: Discussionsupporting
confidence: 50%
“…These are also derived from non-neoplastic melanocytes which become incorporated within these tumors. 11,12 Differentiation of these pigmented tumors is usually not a problem because the cells in these tumors contain tonofilaments and desmosomes while in melanoma these features are absent. The tumor was located in the orbital region of a five-year-old girl and by light microscopy was suspected to be a rhabdomyosarcoma, although no cross striation was demonstrable.…”
Section: Diagnosis Of Malignant Melanomamentioning
confidence: 99%